Integrating LLM-based agents with uncertainty-aware optimization for water-energy-carbon nexus management in irrigation districts - Lei Yu; Zhikai Li; Kai Huang; Fulin Li; Zixiang Lu; Yurui Fan; Yanan Jiang; Chenglong Zhang; Guangtao Fu (Water Research, 2027)

Interface-Engineered CeO2/NiFe LDH hierarchical nanoflowers as robust OER catalysts for practical water splitting - Ruiqian Zhang; Yong Luo; Xin Fu; Ceneng Chen; Yanan Wang; Binbin Qian; Ke Xu; Sridhar Komarneni; Xiaoyan Zhang; Guohua Zhong; Kunfeng Chen; Chunlei Yang; et al. (Fuel, 2026)

Salicylic acid signaling integrates immunity and metabolic regulation to govern nonhost resistance in potato against Phytophthora capsici - Beini Zhang; Huijie Wang; Yanan Huang; Yanhong Fu; Yexin Wu; Juan Du; Hongyang Wang (Plant Science, 2026)

A comprehensive review on PIM-1 membranes for enhanced CO2 separation: strategies for CO2 transport enhancement - Shaohan Lian; Jiangxue Fan; Xiangyun Meng; Boyuan Fu; Siqi Zhang; Jing Han; Tianyang Zhao; Yanan Guan; Erhong Duan; Chunfeng Song (Environmental Research, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Synergistic electrocatalytic reduction-oxidation cascade for efficient degradation of triclosan over an optimal amino-ionic liquid functionalized CoNi/RGO cathode - Dandan Xu; Xueli Xie; Han Zhou; Qin Zhang; Yanan Zhang; Min Huang; Yijian Zhong; Mingming Fu; Shaoyuan Bai (Environmental Research, 2026)

Ionic liquids and SWCNT synergistically construct a dual-transport network in PEDOT: PSS composite fibers for supercapacitor electrodes - Yuxin Fu; Xiuchen Wang; Gege Hang; Yanan Wang; Zhe Liu (Chemical Engineering Journal, 2026)

Mixed-dimensional COF membrane towards fast organic solvent nanofiltration - Fenglong Dai; Tingyuan Wang; Yanan Liu; Xiaocui Wei; Fu Zhao; Enshen Shi; Yigui Du; Chunjia Wang; Shijie Liu; Chunyang Fan; Yuhan Wang; Zhongyi Jiang (Chemical Engineering Journal, 2026)

The efficacy of glycine betaine treatment in alleviating chilling injury in postharvest fruit and vegetables: A systematic review and meta-analysis of recent advances - Xiaodong Fu; Fujun Li; Yanan Li; Xiaoan Li; Xinhua Zhang (Postharvest Biology and Technology, 2026)

Late Triassic tectonic evolution and regional climate response in the northern Tibetan Plateau: Insights into the Triassic–Jurassic mass extinction - Ruiyang Chai; Yanan Zhou; Teng Wang; Qiang Fu; Xiaohua Teng; XiaoJing Yang; Nan Jiang; Qinglong Chen; Zhenwei Chen; Ziwei Bian; Xin Cheng; Jingong Zhang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Caffeic acid-grafted high-amylose maize starch for self-stabilizing emulsion gels: efficient encapsulation and protection of pterostilbene - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Food Chemistry, 2026)

StCYP90C1 modulates plant architecture via regulating brassinosteroid biosynthesis in potato - Qi Fu; Yanan Pu; Jintao Liu; Pei Wu; Juan Wang; Zhong Zhang; Guangtao Zhu (Theoretical and Applied Genetics, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Identification of suitable habitats for the six-spotted mite on rubber trees using multi-source data and MaxEnt modeling - Yanan You; Huichun Ye; Donghua Wang; Chaojia Nie; Jingjing Wang; Bingsun Wu; Fengzheng Cai; Jiajian Deng; Lixia Shen; Fu Wen (Experimental and Applied Acarology, 2026)

Prevalence and Genomic Characterization of mcr-1-Positive Escherichia coli from Livestock in Hunan Province, China (2016–2021) - Jialin Xu; Bohu Yan; Qifu Fu; Haoyu Li; Zonghan Jiang; Rushun Zhou; Xiaojun Chen; Zhiliang Sun; Yanan Wang; Jiyun Li (Current Microbiology, 2026)

Conserved roles of core morphogens in wing formation of the antlion Myrmeleon bore - Wei Dong; YaNan Li; Qiongqiong Zhang; Yuejun Fu; Xu-Bo Zhang (Insect Biochemistry and Molecular Biology, 2026)

AI-guided mining and characterization of plantaricin LP2150: inhibitory mechanism against Shewanella putrefaciens and preservation of large yellow croaker (Larimichthys crocea) - Jie Yang; Yangfan Fu; Shuang Kong; Xiucheng Shang; Meizhong Hu; Antuo Hu; Saikun Pan; Ting Nie; Yanan Liu (Food Control, 2026)

Clinical characteristics and risk factors of severe pulmonary tuberculosis in children in Yunnan, China - Yanan Fu; Feng Jiao; Xiaotao Yang; Yanchun Wang; Linzhen Hu; Lin Gao; Xiaomei Liu; Adong Shen (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Reshaping of the electron transport chain and carbon metabolism by low-loading Fe₃O₄@PU for enhanced phenolic compounds degradation in an algal-bacterial biofilm system - Yanan Fu; Haifeng Zhuang; Jingxin Shi (Journal of Hazardous Materials, 2026)

Assessment and simulation of carbon storage in high-groundwater coal basins based on detailed water body classification: a case study of the Yanzhou Coalfield, China - Yanan He; Yanhua Fu; Li Wang; Wenqi Chen; Wu Xiao; Yichen Shi; Zhengshan Ju (Environmental Monitoring and Assessment, 2026)

A novel Pickering emulsion stabilized solely by n-butyric acid-modified high-amylose corn starch for resveratrol delivery - Liling Fu; Yanan Ren; Conghe Zhang; Wei Yang; Qisheng Tian; Guixiang Zhou; Tian Xu; Changhong Liu; Lei Zheng (Carbohydrate Polymers, 2026)

The evolution of cloud-to-ground lightning and radar reflectivity in mesoscale convective systems over Central-Eastern China - Yanan Fu; Jianhua Sun; Yuanchun Zhang; Shenming Fu; Xiaofang Wang; Chunguang Cui (Atmospheric Research, 2026)

A systematic review and meta-analysis of recent advances: The efficacy of 24-epibrassinolide in preserving postharvest quality of fruit and vegetables - Xiaodong Fu; Fujun Li; Yanan Li; Xiaoan Li; Xinhua Zhang (Trends in Food Science & Technology, 2026)

Bacterial-algae biofilm formation deciphering phenolic wastewater degradation code: Revealing microbial community succession and tripartite synergistic networks - Yanan Fu; Xin Zhou; Jingxin Shi; Haifeng Zhuang (Journal of Water Process Engineering, 2026)

The impact of river habitat stability on benthic macroinvertebrates - Yanan Yu; Bin Fu; Shiming Zhai (Hydrobiologia, 2026)

Freeze-thaw cycles intensified the synergistic inhibitory effects of enrofloxacin and UV-328 on rye seedling growth - Ning Li; Guozhang Bao; Simeng Chen; Yanan Xu; Yue Yuan; Zimin Fu (Journal of Environmental Management, 2026)

Hydrogeochemical characteristics and controlling factors of groundwater in a typical oasis in arid regions - Xing Wei; Qingmei Zhang; Yulin Zhou; Libo Ran; Delun Chen; Xueting Dou; Yanan Fu; Gang Wu (Acta Geophysica, 2026)

Metabolomic remodeling and genetic regulation in potato tubers during domestication - Zhong Zhang; Wei Tan; Jintao Liu; Jiangyue Long; Zefeng Zhai; Yang Feng; Lingling Wei; Hui Du; Qi Fu; Yanan Pu; Pei Wang; Chunzhi Zhang; et al. (Molecular Plant, 2026)

Spatiotemporal Variation Analysis of Yangtze River Basin Water Quality in Chong Qing, China During 2021–2023 Based on Improved Water Quality Assessment - Libo Ran; Xing Wei; Yulin Zhou; Qingmei Zhang; Yanan Fu; Zikan Deng (Water, Air, & Soil Pollution, 2026)

Peniterretonins A-D, terretonin-type meroterpenoids from the marine-derived fungus Penicillium simplicissimum - Yanan Yang; Xiao Han; Peiling Cai; Congcong Zhao; Anran Fu; Kun Liu; Xuli Tang; Guoqiang Li (Phytochemistry, 2026)

The hazards and resource utilization of construction and demolition waste - Yanan Zhang; Bensen Xian; Chenchen Liao; Ruifang Lu; Wenkai Sun; Mei Wang; Shaoyuan Bai; Qin Zhang; Huili Liu; Dandan Xu; Mingming Fu (Journal of Environmental Management, 2026)

Decoding the regulatory role of AmiC in amicoumacins production through transcriptomics and metabolic profiling in Bacillus subtilis fmb60 - Antuo Hu; Yangfan Fu; Di Ren; Haifeng Tang; Qingzheng Zhu; Hucheng Jiang; Yanan Liu; Saikun Pan; Jie Yang; Xiaoying Bian (World Journal of Microbiology and Biotechnology, 2026)

Engineered nanotechnology for epigenetic therapy in cancer treatment - Yan Li; Yang Li; Yuan Tan; Yanan Cai; Xinfeng Liu; Chao Wei; Wenjun Yu; Yuanlei Fu; Haiqiang Cao (Chemical Engineering Journal, 2025)

Morphology-controlled synthesis of WO3 nanosheet arrays/nanonet via in-situ solvothermal reactions for morphology-dependent N2H4/NO2 sensing performance at near room temperature - Yanan Fu; Ping Wang; Dan Zhao; Xiaojing Bai; Lijie Zhao; Lili Sui; Bing Zhao; Yan Jiang; Haixia Yu (Chemical Engineering Journal, 2025)

Chemical and Isotopic Characteristics of Groundwater in Typical Cities of Three Gorges Reservoir Area in China and Its Suitability for Agricultural Irrigation - Xing Wei; Libo Ran; Yulin Zhou; Mengen Chen; Kaiyu Jiang; Yanan Fu (Water, Air, & Soil Pollution, 2025)

Integrating heavy metal concentration and slope gradient for ecological risk assessment in mountainous regions: Insights from China's Dabie Mountain region - Yujing Yang; Yanan Wang; Canling Chen; Minxuan Luo; Zhitao Huo; Feng Wu; Jinhao Fu (Environmental Research, 2025)

Reveal the structure of plants by X-ray imaging and biomedical beamline at SSRF - Guohao Du; Jianfeng Ji; Han Guo; Yanling Xue; Yanan Fu; Biao Deng; Honglan Xie; Tiqiao Xiao (Phytochemistry Letters, 2025)

Integrating and mapping spatial heterogeneity of the ecosystem: a novel approach to indicating environmental threats - Xiaojie Wei; Yanan Zhang; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu (Environmental Research, 2025)

Delivery of Hexaconazole by the Carboxymethylcellulose grafting and Cellulase/pH responsiveness hollow mesoporous silica nanoparticles - Shuang Gao; Xinyu Guo; Fengrui Li; Yu Zhang; Yanan Yu; Ying Fu; Fei Ye (Carbohydrate Polymers, 2025)

Overcoming microbial antagonism: strategic enhancements for dibenzofuran bioremediation - Yanan Wu; Changai Fu; Yan Chen; Xu Wang; Wenhui Zhao; Meng Chen; Li Li (Journal of Environmental Management, 2025)

Adjusting Co ratios to control the unsaturated Mn defects in nanostick-assembled CoOx@MnOx double layered sphere catalysts for highly active photothermocatalysis of acetone/ethyl acetate and NO without ammonia - Yinming Fan; Weihan Wu; Yanping Zhang; Yinian Zhu; Shengpeng Mo; Lei Liao; Mingming Fu; Yanan Zhang; Xiaobin Zhou; Zongqiang Zhu (Journal of Environmental Chemical Engineering, 2025)

Effect of dominant vegetation under long-term natural and artificial vegetation restoration modes on gully slope stability considering rainfall and topography interactions - Lanqian Feng; Yulan Chen; Mingming Guo; Wenlong Wang; Yibao Lou; Zhuoxin Chen; Yanan Zhu; Qianhua Shi; Shaoliang Zhang; Qiang Fu (CATENA, 2025)

LuxR solo regulates recalcitrant aromatic compound biodegradation: Repression and activation of dibenzofuran-catabolic genes expression in a Rhodococcus sp. - Changai Fu; Xu Wang; Yanan Wu; Li Li (Journal of Hazardous Materials, 2025)

Design and Experiment of a Hard-Shell Clam Harvester - Haiyun Wu; Xiaomeng Wang; Bing Huang; Shide Li; Jincheng Hu; Shancan Fu; Lei Yang; Mengxiang Cui; Zhenwei Chen; Yanan Zeng; Yongcheng Jiang; Tao Zhang (Fishes, 2025)
Hard-shell clams are highly valued for their nutritional and economic benefits, leading to an increase in their aquaculture scale. Harvesting these clams manually leads to low efficiency and high labor intensity; thus, a new type of hard-shell clam harvester has been designed to overcome this challenge. Based on biological characteristics and sediment properties of hard-shell clams, a 3D model of the harvester has been created utilizing SolidWorks software (version 2022), which has a working length of 980 mm, an excavation depth range from 0~12 mm, and an angle of entry of 22 degrees. To optimize the efficiency of the machine, a Discrete Element Method (DEM) simulation trial was conducted through a three-factor three-level experiment using EDEM software. Results indicated an optimal harvest efficiency of 91.17% with the machine achieving a running speed of 0.526 m/s, roller speed of 4.772 r/min, and excavation depth of 73.067 mm. Field experiments verified the feasibility of the harvester, demonstrating high accuracy when compared to simulation results.

Hydrogen production by suspension self-rotation enhanced pyrolysis of sludge particles in cyclone - Zhiqin Jiang; Yanan Liang; Shu Zhu; Kai Zheng; Yingjie Zhu; Danhui Yang; Hualin Wang; Pengbo Fu (Water Research, 2025)

Oxygen defect-rich CeO2-x@ZrO2 Mott-Schottky electrocatalyst with tunable interfacial charge redistribution for accelerated sulfur redox kinetics in lithium-sulfur batteries - Shengnan Fu; Chaowei Hu; Yanan Zhang; Jing Li; Hongtao Cui; Yuanyuan Liu; Kaihua Liu; Yanzhao Yang; Meiri Wang (Chemical Engineering Journal, 2025)

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Low molecular weight heparins promote migration and invasion of trophoblast cells through regulating the PI3K/AKT signaling pathway - Qian Zhou; Yanan Zhao; Xiaomin Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cyclodextrin tuned interlayer spacing in covalent organic framework membranes for efficient dye/salt separation - Xiaocui Wei; Yanan Liu; Jianghao Huang; Zongmei Li; Fu Zhao; Zhao Zhang; Tingyuan Wang; Chunyang Fan; Yuhan Yang; Zhongyi Jiang (Desalination, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Fitness and adaptive evolution of a Rhodococcus sp. harboring dioxin-catabolic plasmids - Xu Wang; Changai Fu; Meng Chen; Yanan Wu; Yu Chen; Yan Chen; Li Li (World Journal of Microbiology and Biotechnology, 2025)

Geochemical Characteristics and Hydrocarbon Generation and Expulsion of Oligocene Yacheng Formation Source Rocks in the Northern Yinggehai Basin - Yanan Wang; Zhipeng Huo; Gaowei Hu; Jianxiang Pei; Lin Wei; Lin Hu; XiaoFei Fu; Weihong Wang; Jianbo Gao; Jingshuang Luo; Jiansheng Li (Natural Resources Research, 2025)

Geological Conditions and Sedimentary Models of Oligocene and Eocene Effective Source Rocks in the Northern Yinggehai Basin - Jianxiang Pei; Gaowei Hu; Zhipeng Huo; Zhihong Chen; Yabing Chen; Xiaofei Fu; Weihong Wang; Haiyu Liu; Yanan Wang; Jingshuang Luo; Guofei Chen (Journal of Marine Science and Engineering, 2025)
The development of the effective source rocks of the Eocene and Oligocene directly determines the oil and gas exploration potential in the northern Yinggehai Basin in China. Based on the analogy with the Hanoi Depression in Vietnam and the Yacheng District in the Qiongdongnan Basin and the comprehensive analysis of self-geological conditions, the development conditions of Eocene and Oligocene source rocks in the northern Yinggehai Basin are examined, focusing on tectonic evolution, sedimentary facies, and the paleoenvironment. Finally, the sedimentary models for the effective source rocks are established. The tectonic activity controlled the formation of the sedimentary deep depression and the migration of the sedimentary trough center, which migrated from east to west and then south from the Eocene to the Oligocene, leading to the sedimentary migration of good muddy source rocks. There are multiple sedimentary facies in favor of source rocks, including lacustrine facies, shallow marine facies, and delta plain swamps. The paleoenvironment indicates that the paleoclimate transitioned from warm and humid to cold and arid, the redox conditions evolved from semi-reducing to oxic, and paleoproductivity increased from the early to late Oligocene. Therefore, the early Oligocene was more conducive to the enrichment of organic matter. It is speculated that the warm and humid paleoclimate, reducing environment, and high paleoproductivity of the Eocene promoted the sedimentation and preservation of more organic matter. The above studies show that the northern Yinggehai Basin, especially the sedimentary period of the Eocene and Oligocene, has favorable geological conditions for the development of effective source rocks. The sedimentary models for Eocene lacustrine mudstones and Oligocene marine mudstones and marine–continental transitional coal-measure source rocks were established. These studies make up for the serious deficiency of previous research and mean that there is great exploration potential for oil and gas in the northern Yinggehai Basin in China.

The exploration of pasteurization processes and mechanisms of inactivation of Bacillus cereus ATCC 14579 using radio frequency energy - Yanan Sun; Yiming Jia; Ke Wang; Songlei Wang; Baozhong Cui; Chao Mao; Xiaoying Guo; Yuxin Feng; Hongfei Fu; Xiangwei Chen; Yequn Wang; Zhenna Zhang; et al. (International Journal of Food Microbiology, 2025)

Microenvironment engineering in carbon nitride supported metal single atoms for solar driven aqueous pollutant removal - Shuaijun Wang; Yanan Dong; Yanjie Fu; Bin Li; Jinqiang Zhang (Chemical Engineering Journal, 2025)

Metabolic profile changes of zebrafish larvae in the single- and co-exposures of microplastics and phenanthrene - Jingyi Li; Xiao Liu; Jing Fu; Zhiyuan Gong; Sabrina Yanan Jiang; J. Paul Chen (Science of The Total Environment, 2024)

Estimation of breakout force of spudcan footing in structured clay - Yanan Xie; Dong Wang; Jingbin Zheng; Dengfeng Fu; Kuntan Chang (Ocean Engineering, 2024)

Programmed DNA tile response system enabled accurate detection of ATP for clinical diagnosis - Dongxia Li; Yanan Peng; Liangqing Lu; Delun Chen; Bingrong Wang; Qiumei Pu; Qionglin Zhou; Xinxin Xiao; Mingpeng Fu; Xiaohong Wang; Jinchun Tu; Hua Pei; et al. (Chemical Engineering Journal, 2024)

Anthropogenic shrub encroachment has accelerated the degradation of desert steppe soil over the past four decades - Yanan Zhao; Hongmei Wang; Zhigang Li; Gang Lin; Jingying Fu; Zhili Li; Zhenjie Zhang; Dong Jiang (Science of The Total Environment, 2024)

Preparation of plant-derived compounds/chitosan/gelatin antifungal film and investigation of its control effect on Zygosaccharomyces rouxii contamination in concentrated apple juice - Huxuan Wang; Xuanzhi Wang; Jing Dong; Jiaxuan Fu; Tiantian Zhao; Yanan Zhu; Dawei Chang (Food Bioscience, 2024)

Microenvironment design strategies for enhanced CO2 electroreduction with a 60% full-cell energy efficiency - Pengtao Yue; Junjun Wu; Chaozhong Qin; Bowen Shi; Yang Wang; Yue Zhang; Yanan Zou; Jun Li; Liang Zhang; Xun Zhu; Miao Zhong; Qian Fu; et al. (Chemical Engineering Journal, 2024)

Effect of hot air-assisted radio frequency rotation heating system on improving heating uniformity of dried black fungus (Auricularia auricula) - Zheng Geng; Yingman Xie; Pengfei Ye; Yanan Sun; Hongfei Fu; Xiangwei Chen; Yequn Wang; Yunyang Wang (Food and Bioproducts Processing, 2024)

Evidence for low sulfate and anoxic deep waters in early Cambrian - Yizhe Gong; Dandan Li; Menghan Li; Lilin Sun; Xiaolin Zhang; Yawen Cui; Yong Fu; Yilun Xu; Yanan Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mechanisms and high-value applications of phthalate isomers degradation pathways in bacteria - Qiu Lequan; Fu Yanan; Zhou Xianda; Bao Mengyuan; Li Chenyu; Wu Shijin (World Journal of Microbiology and Biotechnology, 2024)

Formation Mechanisms of the Extreme Rainfall and Mesoscale Convective Systems over South China during the Dragon Boat Rainy Season of 2022 - Yanan Fu; Jianhua Sun; Zhifang Wu; Tao Chen; Xiaodong Song; Shijun Sun; Shenming Fu (Asia-Pacific Journal of Atmospheric Sciences, 2024)

SlMsrB5-SlGRAS4 involved in methyl jasmonate-mediated ripening and quality of postharvest tomato fruit - Xiaodong Fu; Fujun Li; Maratab Ali; Yanan Song; Jun Ding; Xiangrong Kong; Jing Shang; Xiuming Zhao; Xiaoan Li; Xinhua Zhang (Postharvest Biology and Technology, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Metabolic cross-feeding between the competent degrader Rhodococcus sp. strain p52 and an incompetent partner during catabolism of dibenzofuran: Understanding the leading and supporting roles - Xudi Wang; Yanan Wu; Changai Fu; Wenhui Zhao; Li Li (Journal of Hazardous Materials, 2024)

An intelligent indicating label using mulberry pigment, polylactic acid and rutile TiO2 nanoparticle for monitoring the freshness of cold fresh pork - Huxuan Wang; Jing Dong; Xuanzhi Wang; Jiaxuan Fu; Tiantian Zhao; Yanan Zhu; Dawei Chang; Yungang Cao (Food Bioscience, 2024)

Dynamics of carbon storage driven by land use/land cover transformation in coal mining areas with a high groundwater table: A case study of Yanzhou Coal Mine, China - Yanhua Fu; Yanan He; Wenqi Chen; Wu Xiao; He Ren; Yichen Shi; Zhenqi Hu (Environmental Research, 2024)

Robust augmented estimation for hourly PM$$_{2.5}$$ using heteroscedastic spatiotemporal models - Yanan Song; Jinran Wu; Liya Fu; You-Gan Wang (Stochastic Environmental Research and Risk Assessment, 2024)

Hierarchically ordered microporous Ag2S QDs-CoOx/NC nanostructures for enhancing photocatalytic CO2 reduction to chemical fuels - Shengpeng Mo; Lili Huang; Xin Zhao; Jun Li; Xuegang Ding; Xiaobin Zhou; Yanan Zhang; Yinming Fan; Mingming Fu; Hongxiang Zhu; Qinglin Xie; Daiqi Ye (Fuel, 2024)

A novel detection method for sulfur content in ship fuel based on metal-doped tin oxide quantum dots as fluorescent sensor - Jianqiao Liu; Wenping Li; Hongjin Li; Yanan Zhang; Zhaoxia Zhai; Yang Wang; Ce Fu; Junsheng Wang (Fuel, 2024)

Inhibiting effect of 2-amino-2-methyl-1-propanol on gelatinous product formation in non-aqueous CO2 absorbents: Experimental study and molecular understanding - Chao Liu; Guohua Jing; Zongqiang Zhu; Yinming Fan; Shengpeng Mo; Yanan Zhang; Dunqiu Wang; Bihong Lv; Mingming Fu; Xiaobin Zhou (Chemical Engineering Journal, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Highly-efficient lipid production from hydrolysate of Radix paeoniae alba residue by oleaginous yeast Cutaneotrichosporon oleaginosum - Chen Xu; Yanan Wang; Chuying Zhang; Junheng Liu; Hanqi Fu; Wenting Zhou; Zhiwei Gong (Bioresource Technology, 2024)

Occurrence and correlation of microplastics and dibutyl phthalate in rivers from Pearl River Delta, China - Duojia Wang; Sabrina Yanan Jiang; Changchang Fan; Longshan Fu; Huada Daniel Ruan (Marine Pollution Bulletin, 2023)

Combination of radio frequency heating and antibacterial agents for microorganism control in the production of packaged tofu - Baozhong Cui; Ke Wang; Nan Hu; Yanan Sun; Chao Mao; Pengfei Ye; Huiyun Pang; Yequn Wang; Hongfei Fu; Xiangwei Chen; Yunyang Wang (Food Control, 2023)

Promoting photothermal catalytic CO2 reduction of Cd2In2S5/Cd0.3Zn0.7S heterojunction with encapsulated hydrogen evolution active site by accelerating charge transfer kinetics - Hongbin He; Xiangbo Zhao; Xuan Jian; Hao Zhang; Tianxu Zeng; Bingbing Feng; Yanan Hu; Zhongqiang Yuan; Xiaoming Gao; Feng Fu (Chemical Engineering Journal, 2023)

How internal nutrient loading forms in shallow lakes: Insights from benthic organic matter mineralization - Xiaolong Yao; Runnan Ding; Yongqiang Zhou; Zhengwen Wang; Yanan Liu; Dafang Fu; Lu Zhang (Water Research, 2023)

Particle high-speed self-rotation in cyclones with different diameters and application in catalyst deoiling - Qiong Li; Tingting Cheng; Qiqi Li; Junjie Liu; Yanan Liang; Jianping Li; Xia Jiang; Hualin Wang; Pengbo Fu (Journal of Cleaner Production, 2023)

Designing multi-layered MOF-on-MOF-transformed core double-shell FeSx@ZnS@CoSx heterojunction for enhanced CO2 photoreduction with water vapor - Lili Huang; Shengpeng Mo; Xin Zhao; Jiangjing Zhou; Xiaobin Zhou; Yanan Zhang; Mingming Fu; Yinming Fan; Qinglin Xie; Daiqi Ye; Yunfa Chen (Chemical Engineering Journal, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

Characteristics and sources of PM2.5-bound elements in Shanghai during autumn and winter of 2019: Insight into the development of pollution episodes - Yanan Chen; Xingnan Ye; Yinghui Yao; Zhixiao Lv; Zhenghang Fu; Cheng Huang; Ruoyan Wang; Jianmin Chen (Science of The Total Environment, 2023)

Dominant anatase TiO2 (0 0 1) with rich surface hydroxyls as catalytic active sites for selective catalytic oxidation of cyclohexylamine to cyclohexanone oxime - Wenjin Ni; Dejian Yan; Shangjun Fu; Yanan Wei; Hongyun Yang; Xiaowen Zhang; Fangfang Zhao; Kuiyi You; He'an Luo (Chemical Engineering Journal, 2023)

Effects of radio frequency thawing on the quality characteristics of frozen mutton - Yanan Sun; Yiming Jia; Mingxia Song; Yan Liu; Le Xin; Xiangwei Chen; Hongfei Fu; Yequn Wang; Yunyang Wang (Food and Bioproducts Processing, 2023)

Hollow cavity engineering of MOFs-derived hierarchical MnOx structure for highly efficient photothermal degradation of ethyl acetate under light irradiation - Jun Li; Shengpeng Mo; Xuegang Ding; Lili Huang; Xiaobin Zhou; Yinming Fan; Yanan Zhang; Mingming Fu; Qinglin Xie; Daiqi Ye (Chemical Engineering Journal, 2023)

Biodegradation of phthalate isomers by newly isolated Klebsiella variico SY1 and its functional genomic analysis - Lequan Qiu; Chenyu Li; Yanan Fu; Ying Wang; Zijie Zhang; Zhi Zuo; Ruifeng Chen; Xinge Yin; Tongtong Li; Shijin Wu (International Biodeterioration & Biodegradation, 2023)

Molecular encapsulation of cinnamaldehyde in V-type starch: The role of solvent and temperature - Qing Gao; Yanan Sun; Ruolan He; Jiabao Zheng; Bin Zhang; Chin Ping Tan; Xiong Fu; Qiang Huang (Food Hydrocolloids, 2023)

How anaerobic sludge microbiome respond to different concentrations of nitrite, nitrate, and ammonium ions: a comparative analysis - Runhua Su; Lina Zhou; Lili Ding; Bo Fu; Huimin Fu; Yanan Shuang; Lin Ye; Haidong Hu; Haijun Ma; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Comparison between warm-sector and frontal heavy rainfall events in South China and the objective classification of warm-sector heavy rainfall events - Yanan Fu; Jianhua Sun; Shenming Fu; Yuanchun Zhang (Meteorology and Atmospheric Physics, 2023)

Simultaneous regulation of Li-ion intercalation and oxygen termination decoration on Ti3C2Tx MXene toward enhanced oxygen electrocatalysis for Li-O2 batteries - Shidong Song; Fangfang Yin; Yue Fu; Jiahao Ren; Junjie Ma; Yanan Liu; Run Ma; Wanyu Ye (Chemical Engineering Journal, 2023)

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Predisposition to atrioventricular septal defects may be caused by SOX7 variants that impair interaction with GATA4 - Baolei Li; Zhuoyan Li; Jianping Yang; Nanchao Hong; Lihui Jin; Yuejuan Xu; Qihua Fu; Kun Sun; Yu Yu; Yanan Lu; Sun Chen (Molecular Genetics and Genomics, 2022)

Response of the nuclear xenobiotic receptors to alleviate glyphosate-based herbicide-induced nephrotoxicity in weaned piglets - Shengnan Qiu; Yang Liu; Yanan Gao; Huiyang Fu; Baoming Shi (Environmental Science and Pollution Research, 2022)

Refining the conversion between phase and height in airborne and UAV-borne SAR interferometry - Huiqiang Wang; Jianjun Zhu; Haiqiang Fu; Yanan Yu (International Journal of Remote Sensing, 2021)

Estimation of subcanopy topography based on single-baseline TanDEM-X InSAR data - Huiqiang Wang; Haiqiang Fu; Jianjun Zhu; Zhiwei Liu; Bing Zhang; Changcheng Wang; Zhiwei Li; Jun Hu; Yanan Yu (Journal of Geodesy, 2021)

Gut microbiome alterations and its link to corticosteroid resistance in immune thrombocytopenia - Yanan Wang; Fengqi Liu; Gaochao Zhang; Yan Su; Xueyan Sun; Qi Chen; Chencong Wang; Haixia Fu; Yun He; Xiaolu Zhu; Xiao Liu; Meng Lv; et al. (Science China Life Sciences, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Development of Nitrogen Fertilizer Topdressing Model for Winter Wheat Based on Critical Nitrogen Dilution Curve - Yang Wang; Youliang Ye; Yufang Huang; Yanan Zhao; Ning Ren; Wen Fu; Songhua Yue (International Journal of Plant Production, 2020)

Spatial distribution, pollution levels, and source identification of heavy metals in wetlands of Suzhou Industrial Park, China - Jiawei Xu; Qifan Zhuang; Yao Fu; Yanan Huang; Zhuyou Sun; Zhiyong Liu (Wetlands Ecology and Management, 2019)

Effects of different potassium fertilizers on cadmium uptake by three crops - Kang Wang; Guiping Fu; Yao Yu; Yanan Wan; Zhe Liu; Qi Wang; Jingsuo Zhang; Huafen Li (Environmental Science and Pollution Research, 2019)

Coamorphous Loratadine-Citric Acid System with Enhanced Physical Stability and Bioavailability - Jin Wang; Ruimiao Chang; Yanan Zhao; Jiye Zhang; Ting Zhang; Qiang Fu; Chun Chang; Aiguo Zeng (AAPS PharmSciTech, 2017)

Occurrence and risk assessment of heavy metals in sediments of the Xiangjiang River, China - Jinjun Liu; Youze Xu; Yingxiang Cheng; Yuanyuan Zhao; Yanan Pan; Guangyi Fu; Youzhi Dai (Environmental Science and Pollution Research, 2017)

Cyanidin-3-O-glucoside Induces Apoptosis and Inhibits Migration of Tumor Necrosis Factor-α-Treated Rat Aortic Smooth Muscle Cells - Xuerui Yan; Lin Wu; Bin Li; Xianjun Meng; Hanping Dai; Yanan Zheng; Junfan Fu (Cardiovascular Toxicology, 2016)

Erratum to: Altuibacter lentus gen. nov., sp. nov., a novel member of family Flavobacteriaceae isolated from deep seawater of the South China Sea - Yi Chen; Zilian Zhang; Yingnan Fu; Yanan Wang; Yu Wang; Nianzhi Jiao (Antonie van Leeuwenhoek, 2014)

Altuibacter lentus gen. nov., sp. nov., a novel member of family Flavobacteriaceae isolated from deep seawater of the South China Sea - Yi Chen; Zilian Zhang; Yingnan Fu; Yanan Wang; Yu Wang; Nianzhi Jiao (Antonie van Leeuwenhoek, 2013)

Roseibacterium beibuensis sp. nov., a Novel Member of Roseobacter Clade Isolated from Beibu Gulf in the South China Sea - Yujiao Mao; Jingjing Wei; Qiang Zheng; Na Xiao; Qipei Li; Yingnan Fu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Paracoccus oceanense sp. nov., Isolated from the West Pacific - Yingnan Fu; Qipei Li; Keshao Liu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2011)

Paracoccus beibuensis sp. nov., Isolated from the South China Sea - Qiang Zheng; Yanan Wang; Chuang Chen; Yu Wang; Xiaomin Xia; Yingnan Fu; Rui Zhang; Nianzhi Jiao (Current Microbiology, 2011)